Analysis of polymorphism of innate immunity receptor genes in patients with coronary atherosclerosis and in a population sample from Novosibirsk - S. V. Mikhailova; D. E. Ivanoshchuk; P. S. Orlov; L. D. Latyntseva; E. V. Kashtanova; Ya. V. Polonskaya; Yu. I. Ragino; E. V. Shakhtshneider (Сибирский научный медицинский журнал, 2023)
Understanding the molecular mechanisms of atherosclerotic vascular lesions formation is necessary both for assessing the risks of cardiovascular diseases and for finding approaches to their therapy. The task remains relevant, despite the large number of studies carried out, because there are differences in the factors of genetic predisposition to atherosclerosis and its complications between different ethno-territorial groups. The aim of this study was to search for genetic variants of pattern recognition receptors associated with lipid metabolism disorders that can lead to the development of coronary atherosclerosis (CA).Material and methods. Analysis of exons and adjacent splicing sites of pattern recognition receptors genes in patients with CA (30 men), and then genotyping of a population sample from Novosibirsk (n = 1441) by real-time PCR for selected rs113706342 of the TLR1 gene and analysis of associations of its carriage with lipid metabolism were performed.Results and discussion. The frequency of the minor allele rs113706342 C of the TLR1 gene in the sample of residents of Novosibirsk was 0.0114 ± 0.0062, the carriage of this variant was associated with an increased level of low-density lipoprotein cholesterol in both women and men (p = 0.009 and p = 0.019, respectively). Women carriers of the minor allele C for rs113706342 also had a statistically significant increase in total serum cholesterol (p = 0.013) compared with TT homozygotes. To test the role of this variant in the development of CA, genotyping of an extended sample of patients is required. In one of the patients with CA, a previously undescribed single nucleotide variant chr16:3614637 G/C was found, leading to the Leu101Val substitution in the NLRC3 gene; segregation analysis is required to assess its functional significance.Conclusions. The association of rs113706342 C of the TLR1 gene with lipid metabolism disorders in the Russian population is shown.